A Problem for the Ideal Worlds Account of Desire. (29th November 2021) - Blumberg, Kyle
Abstract: The Ideal Worlds Account of Desire says that S wants p just in case all of S 's most highly preferred doxastic possibilities make p true. The account predicts that a desire report ⌜S wants p⌝ should be true so long as there is some doxastic p -possibility that is most preferred (by S ). But we present a novel argument showing that this prediction is incorrect. More positively, we take our examples to support alternative analyses of desire, and close by briefly considering what our cases suggest about the logic of desire.